Dynamic Behavior Analysis of the Bus with Two-stage Asymmetric Damper Using the Quarter Car Model Subjected to Transient Road Profile - Le, Dinh-Duy; Tran, Huu Nhan (Journal of Technical Education Science, 2023)
The influences of two-stage asymmetric damper on the dynamic responses under transient road inputs in range of different vehicle velocities were investigated. This study’s purpose is to get full understanding of the dynamic behavior of the bus using the two-stage asymmetric damper. The body’s vibration acceleration, the tire dynamic load coefficient, and the suspension dynamic deflection were all analyzed to determine how much vibration was conveyed to the bus. By evaluating these criteria, this paper shows how the two-stage asymmetric damper affected an inner-city bus’s vibrational behavior. The transient input was employed in accordance with the GB/T 4970-2009 and IRC-99-1988 standards. For the purposes of the investigation, the two degrees of freedom quarter car model has been employed to carry out the simulation. According to the analysis's findings, a two-stage asymmetric damper maintains the better ride comfort level but offers the bus less handling stability and working space than a linear symmetric one.